2018
DOI: 10.1111/rda.13372
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in Saint Croix male lamb reproductive development in northern Mexico

Abstract: ContentsThe aim of this study was to determine the influence of the season of birth on the body weight, testicular size, testosterone concentrations, semen output and sexual behaviour in Saint Croix male lambs. Thirty-three lambs were born in spring (n = 10), summer (Sum; n = 12) or autumn (n = 11). Body weight and the scrotal circumference were weekly recorded; semen was also weekly collected by electroejaculation; and sexual behaviour towards oestrous ewes was weekly evaluated. Data were recorded from 15 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…It is also important to note that the second stage of this study was carried out at the start of the natural breeding season (June-August) when lambs may express higher sexual activity. The study carried out by Sánchez et al (2019) showed that the reproductive performance of Saint Croix male lambs born in spring was better than that of lambs born in summer and autumn. The results reported by Santos et al (2015) and Sanchez et al (2019) suggest that there is a significant effect of an interaction between birth season and weaning method on the sexual behavior and semen quality of male lambs, and this should be a matter of future research.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is also important to note that the second stage of this study was carried out at the start of the natural breeding season (June-August) when lambs may express higher sexual activity. The study carried out by Sánchez et al (2019) showed that the reproductive performance of Saint Croix male lambs born in spring was better than that of lambs born in summer and autumn. The results reported by Santos et al (2015) and Sanchez et al (2019) suggest that there is a significant effect of an interaction between birth season and weaning method on the sexual behavior and semen quality of male lambs, and this should be a matter of future research.…”
Section: Discussionmentioning
confidence: 98%
“…This difference may be explained by an early intake of fibrous components in the diet that favored the development of the rumen (Urbano et al, 2017), which in turn could increase the assimilation of nutrients that favored the development of this characteristic in the ejaculate (Blache and Martin, 2009). Another possible explanation for not finding significant effects of the weaning method on sexual behavior and semen quality is that regardless of the weaning method, male lambs are less stressed than females (Freitas-de-Melo and Ungerfled, 2020), in such a way that other possible factors are involved in this reproductive process (Sánchez-Dávila et al, 2019). For example, Saint Croix lambs are reported to be sexually precocious (Wheaton and Godfrey, 2003) and adapted to different environments; therefore, it is considered that although the SCD lambs were more stressed, and developed more slowly, this was not an impediment for them to develop sexually in a similar way to the CS lambs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation